Sawdust Drying in a Series of Rectangular Base Spouted Beds Using Solar Energy - Reyes-Salinas, A; Henriquez-Vargas, L; Pailahueque-Barahona, N; Gatica-Candia, E (Elsevier Ltd, 2022)
The present work reports experimental results and a statistical analysis of sawdust drying in a direct contact dynamic dryer using solar energy and phase change materials. The equipment consists of a solar energy accumulator using paraffin wax as storage material, and three rectangular base spouted beds connected in series. Solar energy was captured by the energy accumulator in its charging stage and then released as thermal energy to the circulating air, which subsequently entered the rectangular base spouted beds removing moisture from sawdust particles in a continuous operation. Temperature profiles of the paraffin wax and of the air were registered in different positions of the solar energy accumulator. A total of 89 kg of paraffin wax distributed in 450 beverage cans within the accumulator were used. With a confidence level of 95%, it was found that the significant effects in steady state operation were the sawdust feed flow, the solid initial moisture content and the drying air temperature. Using the optimal operating conditions of the dryer found, it was possible to remove 27.6% of the moisture from the solid. Additionally, it was projected that the operation may be feasible for at least 4 h with the amount of accumulated solar energy and with high thermal drying efficiencies. © 2022 Elsevier Ltd